TINDAK TUTUR DIREKTIF DALAM PROSES PEMBELAJARAN DI TAMAN KANAK-KANAK NEGERI IDHATA CIPOTAKARI KABUPATEN SIDENRENG RAPPANG - Nurul Ameliah; Muhammad Hanafi; Yusmah Yusmah; Suleha Suleha (Universitas Negeri Makassar, 2024)
This research aims to describe the form and function of directive speech acts. This research uses a descriptive method with a qualitative approach. The focus of this research is the form and function of directive speech acts in communication between teachers and students at Idhata State Kindergarten Cipotakari, Sidenreng Rappang Regency, during the learning process. The data in this study are the utterances obtained by teachers and students. While the data sources are teachers and students at Idhata Cipotakari State Kindergarten, Sidenreng Rappang Regency during the learning process, The data collection techniques are recording, listening, and transcribing. The results showed that the speech of teachers and students during the learning process is an interaction that contains the intent or meaning it wants to convey. The data obtained in this research is directive speech. There are 3 forms of directive speech acts, namely news speech, question speech, and command speech, and there are 6 types of directive speech acts, namely question speech, command speech, prohibition speech, advice speech, request speech, and permission-giving speech.